The Implementation of Project Based Learning Strategy in Teaching Spoken English - Fajarika Nuninsari, Dessi; Sutopo, Djoko; Anggani Linggar Bharati, Dwi (Universitas Negeri Semarang, 2020)
Project-Based Learning is a learning model in 2013 curriculum that provides an opportunity for students to actively participate in making a project within the group or individual work to improve English language skills, especially in spoken English. The objectives of this study are to explain; 1) the Implementation of project topic stimulation in project based learning, 2) the implementation of project planning design in project based learning, 3) the implementation of schedule arrangement in project based learning, 4) the implementation of project monitoring in project based learning, 5) the implementation of project assessment in project based learning, and 6) the implementation of project evaluation in project based learning. This study was a descriptive qualitative method. The data were collected by implementing observation, field note, document analysis, questionnaire, speaking transcription, and interview. The subjects were an English teacher of SMA Futuhiyyah Mranggen. The result of the study showed that; 1) the English teacher of Futuhiyyah Senior High Schools have implemented the topic stimulation to begin the project. 2) The project design planning is implemented to create the project design for students. 3) The schedule arrangement should be planned to make the project run well. 4) The teacher’s project monitoring should be implemented in order to guide the students’ process in doing the project 5) the project’s assessment should be implemented to know the students’ result in doing the project and 6) the teacher’s evaluation was intended to check whether the students understand or not about the project.